The Roots of Social Conflict in North Maluku (1999-2004) Ethnic Religious Rivalry and Political Power Struggle - Abubakar Muhammad Nur (Greenation International Journal of Law and Social Sciences, 2026)
This study analyzes the roots and escalation of social conflict in North Maluku during 1999–2004 and examines the relevance of educational approaches in addressing ethnic rivalry, religious polarization, and local political competition. The study employed a qualitative method through literature review and analysis of historical documents obtained from secondary sources. Data were collected from records of conflict dynamics, local government policies, and socio-political developments in North Halmahera. The analysis used a descriptive-analytical approach to identify patterns of conflict, the roles of political actors, and structural factors contributing to communal violence. The findings reveal that the conflict was not solely caused by religious differences, but was strongly influenced by political elite competition, struggles over economic resources, especially mining, and the mobilization of ethnic and religious identities to gain political legitimacy. The study also indicates that the absence of effective educational frameworks promoting tolerance, social cohesion, and civic awareness contributed to the escalation of violence. Therefore, the study emphasizes the importance of peace education, multicultural education, and critical civic education as strategic approaches to support social reconciliation and inclusive local governance.